Phantomless estimation of bone mineral density on computed tomography: a scoping review - Waqar, Aleena; Bazzocchi, Alberto; Aparisi Gómez, Maria Pilar (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2025)
Age-related conditions like osteoporosis have become more familiar with increasing global life expectancy. Osteoporosis is characterized by reduced bone mineral density and structural weakening of bone tissue that leads to a higher risk of fracture. Dual-energy X-ray absorptiometry is the current standard for diagnosing osteoporosis. Computed tomography provides an alternative for diagnosis, but traditional QCT involves the use of phantoms, which does not allow retrospective or opportunistic assessments of BMD. This study aims to provide an overview of the evidence and feasibility for emerging phantomless techniques for the estimation of BMD on CT.A scoping review was conducted to evaluate the feasibility and effectiveness of phantomless BMD estimation using CT. A comprehensive search of Scopus and PubMed databases focused on literature published between 2010 and 2024. Search terms included combinations of “phantomless”, “BMD estimation”, and “CT”. Studies emphasizing accuracy, reliability, and clinical feasibility were included. The review identified 26 relevant studies examining methods of phantomless BMD estimation. The majority of the studies used internal anatomical references to calibrate BMD measurements. These methods demonstrated accuracy comparable to traditional phantom-based techniques. Limitations of the technique included variability in scanner types and inconsistencies caused by patient-specific factors like body composition and contrast agents.Phantomless BMD estimation methods are a feasible approach to detecting osteoporosis. The possibility to be integrated into routine CT workflows make them an attractive option for opportunistic screening. Further research is necessary to refine methods, ensure consistent results across different clinical settings, and address outstanding issues such as scanner variability and the effects of contrast agents.
Keywords: osteoporosis; phantomless; BMD; internal calibration; opportunistic